Colorimetric method for determining MICs of antimicrobial agents for Mycobacterium tuberculosis. - Yajko, D M (1995)
A colorimetric method for quantitative measurement of the susceptibility of Mycobacterium tuberculosis to antimicrobial agents is described. The method utilizes an oxidation-reduction dye, Alamar blue, as an indicator of growth. By this method, MICs of isoniazid, rifampin, streptomycin, and ethambutol were determined for 50 strains of M. tuberculosis. Colorimetric MIC results were available on the 7th, 10th, or 14th day of incubation for 29 (58%), 14 (28%), and 7 (14%) of the 50 strains, respectively. When MIC susceptibility results were compared with results obtained by the agar proportion method, increased levels of resistance detected by agar proportion were associated with higher MICs obtained by the colorimetric method. Tentative interpretive criteria for colorimetric MIC results which showed good agreement with results obtained by the agar proportion method were established. Interpretive agreement between the two methods was 98% for isoniazid, rifampin, and ethambutol and 94% for streptomycin. Overall, there was agreement between the two methods for 194 of 200 test results (97%). The colorimetric method is a rapid, quantitative, nonradiometric method for determining the antimicrobial susceptibility of M. tuberculosis.